Evaluadores Volúmen 34(2) (RUNA, archivo para las ciencias del hombre, 2013)
Evaluadores ExtranjerosAlicia González de Castells - UFSC, BrasilJorge Alfredo Hidalgo Lehuede - UChile, ChileMaria Dolores Marrodán - UCM, EspañaEloísa Martín - UFRJ, BrasilElizabeth Pissolato - UFJF, BrasilHenry Tantaleán - UNMSM, PerúMárnio Teixeira-Pinto - UFSC, Brasil Izabela Tomaso - UFRJ, BrasilEvaluadores NacionalesGabriela Caretta - UNSaDelia Lomaglio - UNCa Carlos Masotta - INAPL